195k views
9 votes
Could you tell me the answer of 3(b)? Pleaseeeeee

Could you tell me the answer of 3(b)? Pleaseeeeee-example-1
User Russbear
by
5.0k points

1 Answer

11 votes

Answer:

(b)


\displaystyle (2005)/(2006)

Explanation:

(a)

First, we have to prove that:


\displaystyle (1)/(x)-(1)/(x+1)=(1)/(x(x+1))

Operate:


\displaystyle (1)/(x)-(1)/(x+1)=(x+1-x)/(x(x+1))

Simplifying:


\displaystyle (1)/(x)-(1)/(x+1)=(1)/(x(x+1)) [1]

(b)

Now we use the above expression to find the sum:


\displaystyle S=(1)/(1* 2)+(1)/(2* 3)+(1)/(3* 4)+...+(1)/(2005* 2006)

Let's use [1] for each term of the sum:


\displaystyle (1)/(1* 2)=(1)/(1)-(1)/(2)


\displaystyle (1)/(2* 2)=(1)/(2)-(1)/(3)


\displaystyle (1)/(3* 4)=(1)/(3)-(1)/(4)


\displaystyle (1)/(2005* 2006)=(1)/(2005)-(1)/(2006)

Substituting:


\displaystyle S=(1)/(1)-(1)/(2)+(1)/(2)-(1)/(3)+(1)/(3)-(1)/(4)+....+(1)/(2005)-(1)/(2006)

Note the terms 1/2 and -1/2, 1/3 and -1/3, etc. are canceled out, leaving only the first and last terms:


\displaystyle S=(1)/(1)-(1)/(2006)=(2006-1)/(2006)


\boxed{\displaystyle S=(2005)/(2006)}

User Akash Kava
by
4.7k points